Pelatihan Tajwid Al-Qur’an Dengan Metode At-Tanzil Bagi Guru Ngaji Klompang Barat Kecamatan Pakong Pamekasan - Mohammad Ruslan (Sekolah Tinggi Agama Islam Al-Muntahy, 2025)
This study aims to enhance the competence of Qur’anic teachers (guru ngaji) in reading and teaching the Qur’an in accordance with tajwid rules through a training program based on the At-Tanzil Method in Klompang Barat Village, Pakong District, Pamekasan Regency. The research focuses on empowering Qur’anic teachers to identify and apply systematic and practical tahsin methods in teaching within local Qur’anic learning centers (TPQ). This study employs a descriptive qualitative approach using action research methods. The participants consist of 20 Qur’anic teachers selected purposively. Data were collected through observation, in-depth interviews, documentation, and pre- and post-training reading tests. The results indicate that the implementation of the At-Tanzil Method significantly improved participants’ understanding of tajwid principles, articulation of Arabic letters (makhraj), and confidence in reciting the Qur’an publicly. The training also yielded positive social outcomes, including the establishment of a learning community that functions as a platform for ongoing peer mentoring and collaboration. The implications suggest that the At-Tanzil Method is an effective alternative for tajwid training in rural areas. It is expected that this training model can be replicated in other regions with similar conditions and serve as a reference for developing more contextual and sustainable Qur’anic education methods.